Therapeutic Potentials of Scavenger Receptor CD36 Mediated Innate Immune Responses Against Infectious and Non-Infectious Diseases - Banesh, Sooram; Trivedi, Vishal (Current Drug Discovery Technologies, 2020)
CD36 is a multifunctional glycoprotein, expressed in different types of cells and known to play a significant role in the pathophysiology of the host. The structural studies revealed that the scavenger receptor consists of short cytosolic domains, two transmembrane domains, and a large ectodomain. The ectodomain serves as a receptor for a diverse number of endogenous and exogenous ligands. The CD36-specific ligands are involved in regulating the immune response during infectious and non-infectious diseases in the host. The role of CD36 in regulating the innate immune response during Pneumonia, Tuberculosis, Malaria, Leishmaniasis, HIV, and Sepsis in a ligand- mediated fashion. Apart from infectious diseases, it is also considered to be involved in metabolic disorders such as Atherosclerosis, Alzheimer’s, cancer, and Diabetes. The ligand binding to scavenger receptor modulates the CD36 down-stream innate immune response, and it can be exploited to design suitable immuno-modulators. Hence, the current review focused on the role of the CD36 in innate immune response and therapeutic potentials of novel heterocyclic compounds as CD36 ligands during infectious and non-infectious diseases.
Keywords: phagocytosis